2018
DOI: 10.1111/pbi.12882
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis and regulatory hierarchy of phased small interfering RNAs in plants

Abstract: SummarySeveral varieties of small RNAs including microRNAs (miRNAs) and small interfering RNAs (siRNAs) are generated in plants to regulate development, genome stability and response to adverse environments. Phased siRNA (phasiRNA) is a type of secondary siRNA that is processed from a miRNA‐mediated cleavage of RNA transcripts, increasing silencing efficiency or simultaneously suppressing multiple target genes. Trans‐acting siRNAs (ta‐siRNAs) are a particular class of phasiRNA produced from noncoding transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 102 publications
0
85
0
Order By: Relevance
“…Finally, what functions might drive the diversification of phasiRNA sequence composition? Recent reports on phasiRNAs suggest a role in DNA methylation (Dukowic‐Schulze et al ., ; Deng et al ., ). Dukowic‐Schulze et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, what functions might drive the diversification of phasiRNA sequence composition? Recent reports on phasiRNAs suggest a role in DNA methylation (Dukowic‐Schulze et al ., ; Deng et al ., ). Dukowic‐Schulze et al .…”
Section: Discussionmentioning
confidence: 97%
“…Finally, what functions might drive the diversification of phasiRNA sequence composition? Recent reports on phasiRNAs suggest a role in DNA methylation (Dukowic-Schulze et al, 2016;Deng et al, 2018). Dukowic-Schulze et al (2016) reported that DNA methylation increased at 24-PHAS loci in maize meiocytes, and described a potential role in the regulation of chromosomal structure to promote normal meiosis.…”
mentioning
confidence: 99%
“…These PHAS 63 loci include non-coding TAS genes and genes encoding penta-tricopeptide repeat-containing 64 proteins (PPRs), nucleotide-binding and leucine-rich repeat-containing proteins (NB-LRRs), or 65 MYB transcription factors (Allen and Howell, 2010; Zhai et al, 2011;Xia et al, 2013; Fei et al, 66 2013;Axtell, 2013;Yoshikawa, 2013;Zheng et al, 2015;Komiya, 2017;Liu et al, 2018; Deng 67 et al, 2018). Biogenesis of ta-siRNAs includes initial AGO-dependent miRNA binding at single Axtell, 2013;Fei et al, 2013;Zheng et al, 2015;Xia et al, 2013; de 82 Felippes et al, 2017;Komiya, 2017;Deng et al, 2018). Moreover, miR390 may additionally 83 target and inhibit protein-coding gene transcripts, such as StCDPK1 related to auxin-responsive 84 pathway (Santin et al, 2017).…”
mentioning
confidence: 99%
“…TAS3 miR390-dependent loci in non-vascular land plants: towards a comprehensive reconstruction of the gene evolutionary history. Axtell, 2013;Fei et al, 2013;Zheng et al, 2015;Xia et al, 2013; de 82 Felippes et al, 2017;Komiya, 2017;Deng et al, 2018). Moreover, miR390 may additionally 83 target and inhibit protein-coding gene transcripts, such as StCDPK1 related to auxin-responsive 84 pathway (Santin et al, 2017).…”
mentioning
confidence: 99%